Evaluation of Quality Management System of Bridge Development Project Actors - Novdin M Sianturi; Darwin Sitompul; Syahrizal Syahrizal (Eduvest - Journal of Universal Studies, 2022)
This study is the result of a rehearsal to find the factors that are the main reasons for the delay in the completion of the Sei Wampu Bridge project, Empus Village Project, Bahorok Regency and look for various alternatives to overcome them. By knowing these factors, it is hoped that the company can obtain guidelines for working on subsequent projects so that delays and quality deficiencies can be avoided. The author in this study used a qualitative approach with descriptive delivery. This study uses a descriptive type of research using qualitative methods. Descriptive research is a type of research that describes the actual situation based on data in the field. From the results of the analysis, it can be concluded that problems related to the completion of business achievements that cause not on time and quality are generally caused by 3 (three) factors, namely: the employer factor of the Bridge Construction Project Implementer, the field factor and the order variation factor